Teratoma retroperitoneal en el niño. - Mencia, Luis Felipe; Cazañas, David; Díaz Juan, Pedro; Valdés, Trinidad; Martínez, Ángel; Guernica, Antonio (Revista Cubana de Pediatría, 2022)
Reporte de dos casos